IQRA MOBILE APPLICATION FOR DYSLEXIA CHILDREN (IMAD) - MOHD FADZIL, MOHAMED ASHRAF (IRC, 2019)
Formative dyslexia is a type of reading inability, is a disorder in children which their etiologies are multifactorial, reflecting genetic influences and dysfunction of brain systems and show learning disable for reading. The causes of dyslexia are multifactorial and are hereditary. Thus, it was shown difference brain between people with and without dyslexia that revealed by brain imaging studies. These differences occur in areas of the brain involved with key reading skills. It is one of the commonest learning disorders among school going children. Basically children with dyslexia, indicated poor thresholds for stimuli with low contrasts and poor sensitivity to visual motion.” “The objective of this final year project is to support children with dyslexia have difficulty in reading the Quranic verses by using Iqra which is the basic reading material for Quranic verses. From research and the author discovered majority of the children with dyslexia had difficulty reading the Quranic verses too besides reading English and Malay language. Hence, helpful intervention for Muslim dyslexic children should need to be progress for learning to read the Iqra. The verses in the Iqra are in the Arabic language whereby the letters (Hijaiyah letters) totally different from the alphabets that used in the English and Malay language. So, the author wonder if children with reading difficulties in the Malay language will also have similar difficulties in reading the Iqra as well. So this dyslexic need some application that can help and support them in a way for learning approach. Alternatively, mobile application is considered as greatest way to encourage children with dyslexia to learn and capture it. But, there are lack of existence of mobile application for children with dyslexia in Malaysia. Consequently, this final year project aims to develop a mobile application of dyslexia in Malaysia and to offer the most effective mobile application design for dyslexia children.” “Furthermore, mobile application would be considered as the most effective component for the dyslexia children because of the children nowadays like to spend more time on mobile phone or tablet. So, this will be the best way to design the learning mobile application for dyslexic. The mobile application need to provide an interactive education experience for children with dyslexia to attract them and make it interesting when they learn.